Diagnostic accuracy of inflammation and insulin resistance markers in non-alcoholic fatty liver disease in children - Yu.M. Stepanov; N.Yu. Zavhorodnia; O.M. Tatarchuk; I.A. Klenina; O.P. Petishko (Zaslavsky O.Yu., 2022)
Background. Insulin resistance indices, in particular homeostatic model assessment of insulin resistance (HOMA-IR), and circulating cytokines are promising markers for noninvasive assessment of hepatocyte damage and metabolic risk in non-alcoholic fatty liver disease (NAFLD) in children and can be used to select pediatric patients at risk of adverse disease course. The purpose was to determine the diagnostic accuracy of insulin resistance markers and circulating cytokines in non-alcoholic fatty liver disease in children. Materials and methods. One hundred and seventy patients aged 6-17 (average of 12.15 ± 2.51) years were included in the study. Hepatic steatosis was determined by transient elastography. Patients were divided into 4 groups according to the presence of hepatic steatosis, non-alcoholic steatohepatitis (NASH) and obesity: group 1 - 37 obese children with NASH, group 2 - 53 patients with simple steatosis, group 3 - 65 obese children without steatosis, group 4 (controls) - 15 patients with normal weight without NAFLD. Anthropometric parameters, carbohydrate metabolism with the HOMA-IR calculation, cytokine profile were evaluated. Results. An increase in serum interleukin (IL) 6 and tumor necrosis factor (TNF) α levels in NAFLD children compared to the control group (p < 0.05), a decrease in IL-10 level in patients with NAFLD (p < 0.05), and an increase in TNFα/IL-10 ratio (p < 0.05) in NASH children compared to obese patients without steatosis were demonstrated. In NAFLD children, an increase of HOMA-IR was found compared to the controls and obese patients without steatosis (p < 0.05). The threshold value of HOMA-IR for the diagnosis of simple steatosis was 3.6 (sensitivity 78.6 %, specificity 52.0 %, area under the curve (AUC) 0.687), for the diagnosis of NASH - 4.9 (sensitivity 77.5 %, specificity 61.7 %, AUC 0.750). The threshold value of TNFα/IL-10 ratio for the diagnosis of NASH was 0.58 (sensitivity 75.7 %, specificity 65.7 %, AUC 0.716). Conclusions. The threshold values of HOMA-IR and TNFα/IL-10 ratio demonstrate high diagnostic accuracy and can be used for early non-invasive diagnosis of NAFLD in obese children and for differential diagnosis of simple steatosis and NASH.